Successful Sonography-Guided Fine-Needle Aspiration Biopsy of a 1-Millimeter-Diameter Papillary Thyroid Microcarcinoma - Kim, D.W.; Kim, S.H.; Jung, S.J. (American Journal of Neuroradiology, 2010)
SUMMARY: A PTMC is defined as a thyroid papillary cancer that measures ≤10 mm in the greatest diameter. The detection rate for a PTMC has increased because of the worldwide use of high-resolution sonography and US-FNAB. We report a case of a 1-mm-diameter PTMC confirmed at thyroidectomy for which the cytologic diagnosis had an important role in deciding the extent of surgery (ie, either a total thyroidectomy or a hemithyroidectomy). ATAAmerican Thyroid AssociationHEhematoxylin-eosinPTCpapillary thyroid carcinomaPTMCpapillary thyroid microcarcinomaUS-FNABsonography-guided fine-needle aspiration biopsy